Facha lore: Memes as memory creation technique in Vox - Soriano , Ezequiel; Pichel-Vázquez, Alexandre (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2025)
The presence of the Spanish far right is no longer extraordinary, and social networks have had a key role. Departing from the vernacular digital concept of ‘lore’, we analyze how Vox creates a living narration, a feeling, or an atmosphere that mythologizes the party’s history and figure, generating a collective memory. This article shows how Vox deploys memes on the Internet as a way of self-mythologization and memory construction. This analysis emerges from the ethnographic observation of the ‘meme’s booth’, a physical structure full of setups and screenshots. Vox put these memes to easily disseminate its imaginary during the political festivity VIVA21. In this booth, memes are not only multimedia that communicate some claims, but also a form of online communication that defines a way of being and renews the party’s collective narration.